Efektifitas SIMPUS Terhadap Pelayanan Kesehatan Primary Care BPJS di UPTD Puskesmas Unaaha Tahun 2020 - mashuriposimbi@gmail.com; Herlina Abidin; Sri Ujiatin Lasahari (Pengurus Daerah Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI) Sulawesi Tenggara, 2021)
UPTD Unaaha Center is one of the centers that has applied SIMPUS to Primary Care BPJS Health Services since 2014, which to support the performance of service of BPJS in the Middle East, the system is implemented by all exiting micro finance institutions in Indonesia, include in 24 PHC of the 2014 Konawe district but not all navel can apply the application is caused by internet access. As for peak attendence in 2020 workplace of Unaaha PHC beginning in February 15. 223 people, beginning in march 15.037 people, beginning in April 15.061 people, beginning in May 14.570 people, beginning in June 14.862 people and beginning in july 14.822 people.The Unaaha PHC has applied a bridging system it’s integrated data between SIMPUS and PCare (link card sections to the general clinic link to SIMPUS link sections to the business design section). Research was carried out in August 2020.The data collected is descrevtive data. Inductive data analysis. Six informers it’s the key informant the head of the center, the usual informant covers: the bussines administration, the registration office, the reporting and medical personnel of the patients and BPJS officer Konawe district. While the object is the BPJS Health Management Information System of PCare at the Konawe district.